PERANAN BATIK BAKARAN SEBAGAI CENDERAMATA KHAS KECAMATAN JUWANA - Pranata Darma, I Gusti Ketut Indra (Jurnal Akademi Pariwisata Medan, 2020)
There are several factors that make a product can be categorized as a souvenir typical of a region. Among them is having the distinctiveness of a place or unique, relative price, can be carried by hand, has a value of reminiscence, is able to be awarded and have the memory of events from somewhere. Typical regional products Juwana one of them is Batik Offering. This study aims to determine whether Batik Bakaran fulfills the criteria for a souvenir and development efforts. The study was conducted using qualitative method by conducting depth interviews with informants. Informants are looking for is a trader and craftsmen Batik Bakaran, and buyers who frequently use the product Batik Offering. Based on research data obtained, Batik Bakaran can be called as souvenirs of the District Juwana because it has a strong characteristic 5 of the 6 available. For development efforts that have been made for this, among others, by utilizing technology to introduce the product, participated in the exhibition to get a new variation of the motif.